(untitled) (Global Journal of Management and Business Research, 2020)
In a highly competitive environment and competing with large, resource-rich companies, companies of all sizes focus on finding resources for both creating and maintaining competitive advantages. Psychological profile is therefore strategic resource that enables SMEs to establish a sustainable competitive advantage. The purpose of this work is in the context of research that supports the existence of a positive psychological profile and entrepreneurial innovation of SMEs. Specifically, this study aims to evaluate the effect of psychological profile on the entrepreneurial innovation of SMEs. To answer this problem, we started from a theoretical framework to express our hypotheses